Achieving Business Excellence by Optimizing Corporate Forensic Readiness - Gojko Grubor; Ivan Barać; Nataša Simeunović; Nenad Ristić (Amfiteatru Economic Journal, 2017)
In order to improve their business excellence, all organizations, despite their size (small, medium or large one) should manage their risk of fraud. Fraud, in today's world, is often committed by using computers and can only be revealed by digital forensic investigator. Not even small or medium-sized companies are secure from fraud. In the light of recent financial scandals that literary demolished not just economies of specific countries but entire world economy, we propose in this paper an optimal model of corporative computer incident digital forensic investigation (CCIDFI) by using adopted mathematic model of the greed MCDM – multi-criteria decision-making method and the Expert Choice software tool for multi-criteria optimization of the CCIDFI readiness. Proposed model can, first of all, help managers of small and medium-sized companies to justify their decisions to employ digital forensic investigators and include them in their information security teams in order to choose the optimal CCIDFI model and improve forensic readiness in the computer incident management process that will result with minimization of potential losses of company in the future and improve its business quality.
Keywords: C39; G32; M15; 330; computer incident; forensic readiness; forensic alternatives; forensic criteria; greed multi-criteria method; Expert Choice evaluation